2022
DOI: 10.1371/journal.pone.0276286
|View full text |Cite
|
Sign up to set email alerts
|

A systemic review and network meta-analysis of accuracy of intraocular lens power calculation formulas in primary angle-closure conditions

Abstract: Background For primary angle-closure and angle-closure glaucoma, the fact that refractive error sometimes deviates from predictions after intraocular lens (IOL) implantation is familiar to cataract surgeons. Since controversy remains in the accuracy of IOL power calculation formulas, both traditional and network meta-analysis on formula accuracy were conducted in patients with primary angle-closure conditions. Methods A comprehensive literature search was conducted through Aug 2022, focusing on studies on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Eyes with glaucoma are associated with extremes in AL, with open angle glaucoma associated with high myopia [ 91 ] and increased AL [ 92 ], while angle-closure eyes have been shown to have shorter ALs [ 93 ]. Extreme ALs may, in the past, have been associated with increased risk of IOL calculation errors; however, modern IOL formulae have proven accurate even for extreme axial lengths, and they may lessen the influence of AL on the accuracy of IOL power calculations [ 94 , 95 ]. In a network meta-analysis, Lu et al [ 95 ] investigated eight formulae: including Barrett Universal II, Kane, SRK/T, Hoffer Q, Haigas, Holladay I, Hill-Radial Basis Function (RBF 3.0) and Ladas Super Formula (LSF) used for IOL power calculations in eyes with PACG and found no significant differences in outcomes among all the above formulae.…”
Section: Discussion: Considerations In Premium Iol Implantation In Gl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Eyes with glaucoma are associated with extremes in AL, with open angle glaucoma associated with high myopia [ 91 ] and increased AL [ 92 ], while angle-closure eyes have been shown to have shorter ALs [ 93 ]. Extreme ALs may, in the past, have been associated with increased risk of IOL calculation errors; however, modern IOL formulae have proven accurate even for extreme axial lengths, and they may lessen the influence of AL on the accuracy of IOL power calculations [ 94 , 95 ]. In a network meta-analysis, Lu et al [ 95 ] investigated eight formulae: including Barrett Universal II, Kane, SRK/T, Hoffer Q, Haigas, Holladay I, Hill-Radial Basis Function (RBF 3.0) and Ladas Super Formula (LSF) used for IOL power calculations in eyes with PACG and found no significant differences in outcomes among all the above formulae.…”
Section: Discussion: Considerations In Premium Iol Implantation In Gl...mentioning
confidence: 99%
“…Extreme ALs may, in the past, have been associated with increased risk of IOL calculation errors; however, modern IOL formulae have proven accurate even for extreme axial lengths, and they may lessen the influence of AL on the accuracy of IOL power calculations [ 94 , 95 ]. In a network meta-analysis, Lu et al [ 95 ] investigated eight formulae: including Barrett Universal II, Kane, SRK/T, Hoffer Q, Haigas, Holladay I, Hill-Radial Basis Function (RBF 3.0) and Ladas Super Formula (LSF) used for IOL power calculations in eyes with PACG and found no significant differences in outcomes among all the above formulae. Studies have also shown that greater changes in ACD may occur post-operatively in eyes with a pre-operatively shallow ACD (<2.5 mm) and a shorter AL (<23 mm), and that this was associated with a higher risk of refractive error after cataract surgery [ 96 ].…”
Section: Discussion: Considerations In Premium Iol Implantation In Gl...mentioning
confidence: 99%